2014
DOI: 10.1016/j.jinorgbio.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

A cisplatin slow-release hydrogel drug delivery system based on a formulation of the macrocycle cucurbit[7]uril, gelatin and polyvinyl alcohol

Abstract: The anticancer drug cisplatin was encapsulated within the cucurbit [7]uril macrocycle to form the host-guest complex: cisplatin@CB [7]. This was then incorporated into gelatin and 0-4% w/v polyvinyl alcohol (PVA)-based hydrogels as slow release drug delivery vehicles. The hydrogels demonstrated predicable swelling and disintegration dependent on the PVA concentration. The hydrogel with the highest PVA content was slower to swell and release drug compared with lower concentrations of PVA. The effect of the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 31 publications
0
35
0
Order By: Relevance
“…Cucurbit [7]uril has been formulated into gelatin-and polyvinyl alcohol (PVA)-based hydrogels (40). When used to form a host-guest complex with the anticancer drug cisplatin, the subcutaneous implantation of the hydrogels meant that they were able to act as a slow release delivery system.…”
Section: Cucurbituril Pharmaceutical Dosage Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cucurbit [7]uril has been formulated into gelatin-and polyvinyl alcohol (PVA)-based hydrogels (40). When used to form a host-guest complex with the anticancer drug cisplatin, the subcutaneous implantation of the hydrogels meant that they were able to act as a slow release delivery system.…”
Section: Cucurbituril Pharmaceutical Dosage Formsmentioning
confidence: 99%
“…When used to form a host-guest complex with the anticancer drug cisplatin, the subcutaneous implantation of the hydrogels meant that they were able to act as a slow release delivery system. An in vivo human ovarian cancer model using the hydrogels demonstrated that they were highly effective, with a 2% PVA formulation with cisplatin@CB[7] (10) being just as effective as a 5 x higher dose of free cisplatin delivered via an intraperitoneal injection (40).…”
Section: Cucurbituril Pharmaceutical Dosage Formsmentioning
confidence: 99%
“…Later on, we used the molds to fabricate degradable microneedle patch with polyvinyl alcohol (PVA). PVA is a water-soluble polymer with wide practical application in a variety of fields, including wound dressing, implants, cell encapsulation, drug-delivery systems, soft contact lenses and dental applications, due to its excellent chemical resistance and physical properties, low toxicity and high biocompatibility [14][15][16] . An aqueous solution of PVA can form hydrogels through cast-drying process, where PVA physically cross links during the dehydration process 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a superabsorbent can absorb abundant water or other aqueous solutions. Because of superior properties compared to traditional materials such as sponges, they are widely used in hygiene (Kosemund et al 2009), agriculture (Guo et al 2005;Liang et al 2009), drug delivery (Reddy et al 2011;Oun et al 2014), and water purification (Zheng et al 2010;Wang et al 2011). The research on the use of superabsorbents as water and fertilizer managing materials for the renewal desert environment (Banedjschafie and Durner 2015) and slow release fertilizers (Li et al2016;Yamamoto et al 2016) has attracted great attention, and encouraging results have been observed, as they can reduce irrigation water consumption, lower the death rate of plants, and increase plant growth rate (Parvathy et al 2014).…”
Section: Introductionmentioning
confidence: 99%